Wolfram Alpha:
Search by keyword:
Astronomy
Chemistry
Classical Mechanics
Classical Physics
Climate Change
Cosmology
Finance and Accounting
Game Theory
General Relativity
Group Theory
Lagrangian and Hamiltonian Mechanics
Macroeconomics
Mathematics
Microeconomics
Nuclear Physics
Particle Physics
Probability and Statistics
Programming and Computer Science
Quantum Computing
Quantum Field Theory
Quantum Mechanics
Semiconductor Reliability
Solid State Electronics
Special Relativity
Statistical Mechanics
String Theory
Superconductivity
Supersymmetry (SUSY) and Grand Unified Theory (GUT)
The Standard Model
Topology
Units, Constants and Useful Formulas
Spinors  Part 1
Spinors  Part 2

In Spinors  Part 1 we identified the following:
1. The generators, S^{>ρσ}, are defined as:
S^{ρσ} = (1/4)[γ^{ρ},γ^{σ}]
^{ } = (1/2)γ^{ρ}γ^{σ}  (1/2)η^{ρσ}
2. The Lorentz transformation for a spinor, S[Λ]
S[Λ] = exp((1/2)Ω_{ρσ}S^{ρσ})
3. The Lorentz transformation for a vector, Λ
Λ = exp((1/2)Ω_{ρσ}M^{ρσ})
4. The S^{μν} operates operate on a spinor field, ψ.
Under a Lorentz transformation these fields
transform as:
ψ^{α} = S[Λ]^{α}_{β}ψ^{β}
5. (M^{ρσ})^{μ}_{ν} = η^{ρμ}δ^{σ}_{ν}  η^{σμ}δ^{ρ}_{ν}
6. {γ^{μ},γ^{ν}} = 2η^{μν} ... CLIFFORD ALGEBRA.
7. (γ^{0})^{†} = γ^{0}
8. (γ^{0})^{1} = γ^{0}
9. γ^{0}γ^{μ}γ^{0} = (γ^{μ})^{†}
10. (γ^{i})^{†} = γ^{i}
In addition, we will need:
11. [S^{μν},γ^{μ}] = γ^{μ}η^{νρ}  γ^{ν}η^{ρμ}
Proof:
[S^{μν},γ^{μ}] = (1/2)[γ^{μ}γ^{ν},γ^{ρ}]
^{ } = (1/2)γ^{μ}γ^{ν}γ^{ρ}  (1/2)γ^{ρ}γ^{μ}γ^{ν}
^{ } = (1/2)γ^{μ}{γ^{ν},γ^{ρ}}  (1/2)γ^{μ}γ^{ρ}γ^{ν}
^{ }  (1/2){γ^{ρ},γ^{ν}}γ^{ν} + (1/2)γ^{μ}γ^{ρ}γ^{ν}
Use 6. to get:
^{ } = γ^{μ}η^{νρ}  γ^{ν}η^{ρμ}
12. [S^{μν},S^{ρσ}] = η^{νρ}S^{μσ}  η^{μρ}S^{νσ} + η^{μσ}S^{νρ}  η^{νσ}S^{μρ}
... LORENTZ ALGEBRA
Proof:
[S^{μν},S^{ρσ}] = (1/2)[S^{μν},γ^{ρ}γ^{σ}]
^{ } = (1/2)[S^{μν},γ^{ρ}]γ^{σ} + (1/2)γ^{ρ}[S^{μν},γ^{σ}]
Use 7. to get:
^{ } = γ^{μ}γ^{σ}η^{νρ}  γ^{ν}γ^{σ}η^{ρμ} + γ^{ρ}γ^{μ}η^{νσ}  γ^{ρ}γ^{ν}η^{σμ}
Rearrange 1. γ^{μ}γ^{σ} = 2S^{μσ} + η^{μσ} and substitute to
get:
[S^{μν},S^{ρσ}] = η^{νρ}S^{μσ}  η^{μρ}S^{νσ} + η^{μσ}S^{νρ}  η^{νσ}S^{μρ}
The Dirac Adjoint

Now that we have a field, ψ, we need to construct
a Lorentz scalar and a Lorentz invariant equation
of motion.
If we try and construct a scalar ψψ^{†} we get:.
ψψ^{†} > S[Λ]ψψ^{†}S[Λ]^{†}
The problem with this is that S[Λ]S[Λ]^{†} ≠ 1 and is
certainly not real. To see this consider:
S[Λ] = exp((1/2)Ω_{ρσ}S^{ρσ})
S[Λ]^{†} = exp((1/2)Ω_{ρσ}(S^{ρσ})^{†})
So to be unitary we require (S^{ρσ})^{†} = S^{ρσ}
Unfortunately, this is not possible because γ^{0} is
hermitian whereas the γ^{i}'s are antihermitian.
Therefore, there is no way to pick γ^{μ} such that
all are antihermitian. However, there is a way
around this. Consider:
γ^{0}S[Λ]^{†}γ^{0} = γ^{0}[exp(iΩ_{μν}S^{μν})]^{†}γ^{0}
^{ } = γ^{0}exp((i/2)Ω_{μν}(S^{μν})^{†}γ^{0}
^{ } = γ^{0}(1  (i/2)Ω_{μν}(S^{μν})^{†})γ^{0}
Multiplying from the left and the right gives:
γ^{0}S[Λ]^{†}γ^{0} = 1  (i/2)Ω_{μν}γ^{0}(S^{μν})^{†}γ^{0}
^{ } = exp((i/2)Ω_{μν}γ^{0}(S^{μν})^{†}γ^{0})
Now,
(S^{μν})^{†} = (1/4)[(γ^{μ})^{†},(γ^{ν})^{†}]
^{ } = (1/4)((γ^{μ})^{†}(γ^{ν})^{†}  (γ^{ν})^{†}(γ^{μ})^{†})
^{ } = (1/4)((γ^{0}γ^{μ}γ^{0})(γ^{0}γ^{ν}γ^{0})  (γ^{0}γ^{ν}γ^{0})(γ^{0}γ^{μ}γ^{0}))
^{ } = (1/4)((γ^{0}γ^{μ}γ^{0})(γ^{0}γ^{ν}γ^{0}) + (γ^{0}γ^{μ}γ^{0})(γ^{0}γ^{ν}γ^{0}))
^{ } = (1/2)(γ^{0}γ^{μ}γ^{ν}γ^{0})
^{ } = γ^{0}(1/2)(γ^{μ}γ^{ν})γ^{0}
Therefore,
(S^{μν})^{†} = γ^{0}S^{μν}γ^{0}
Returning to where we left off and using this result we
get:
γ^{0}S[Λ]^{†}γ^{0} = exp((i/2)Ω_{μν}S^{μν})
^{ } = S[Λ]^{1}
Multiplying both sides from the left and the right by γ^{0}
gives:
S[Λ]^{†} = γ^{0}S[Λ]^{1}γ^{0}
With this in mind, we now define the DIRAC ADJOINT:
_
ψ = ψ^{†}γ^{0}
Under a boost we get:
_
ψψ > ψ^{†}S[Λ]^{†}γ^{0}S[Λ]ψ
= ψ^{†}γ^{0}S[Λ]^{1}γ^{0}γ^{0}S[Λ]ψ
= ψ^{†}γ^{0}S[Λ]^{1}S[Λ]ψ
= ψ^{†}γ^{0}ψ
This looks like:
 
 ψ_{1} 
ψ =  ψ_{2} 
 ψ_{3} 
 ψ_{4} 
 
 
ψ^{†} = (ψ^{*})^{T} =  ψ_{1}^{*} ψ_{2}^{*} ψ_{3}^{*} ψ_{4}^{*} 
 
_  
ψ = ψ^{†}γ^{0} =  ψ_{1}^{*} ψ_{2}^{*} ψ_{3}^{*} ψ_{4}^{*} 
 
_
ψψ = ψ_{1}ψ_{1}^{*} + ψ_{2}ψ_{2}^{*}  ψ_{3}ψ_{3}^{*}  ψ_{4}ψ_{4}^{*}
Again, this is completely different to the vector case, x_{μ}x^{μ}.
 ^{ }  
x^{0} x^{1} x^{2} x^{3}  x^{0}  = t^{2}  x^{2}  y^{2}  z^{2}
^{ }   x^{1} 
^{ }  x^{2} 
^{ }  x^{3} 
^{ }  
Bilinears

In the previous section we formed a scalar from 2
spinors. Are they other objects we can form by
combining 2 spinors? The answer is yes. Spinors
can be combined to form scalars, vectors, tensors
and more. The products of two spinors are called
BILINEARS.
Scalar

To form a scalar (spin 0) from 2 spinors one writes:
_
ψψ = ψ^{†}γ^{0}ψ
Under a Lorentz transformation,
_
ψψ > ψ^{†}(Λ^{1}x)S[Λ]^{†}γ^{0}S[Λ]ψ(Λ^{1}x)
= ψ^{†}(Λ^{1}x)γ^{0}ψ(Λ^{1}x)
_
= ψ(Λ^{1}x)ψ(Λ^{1}x)
_
So ψψ does indeed transform as a scalar.
Vector

To form a vector (spin 1) from 2 spinors one writes:
_
ψγ^{μ}ψ
Under a Lorentz transformation,
_
ψγ^{μ}ψ > ψS[Λ]^{1}γ^{μ}S[Λ]ψ
For this to be true we need S[Λ]^{1}γ^{μ}S[Λ] = Λ^{μ}_{ν}γ^{ν} ... 13.
Where,
Λ = exp((1/2)Ω_{ρσ}M^{ρσ}) ~ 1 + (1/2)Ω_{ρσ}M^{ρσ} ...
and,
S[Λ] = exp((1/2)Ω_{ρσ}S^{ρσ}) ~ 1 + (1/2)Ω_{ρσ}S^{ρσ} ...
We work infinitesimally with Ω_{ρσ} = ε_{ρσ}. Therefore,
(1  (1/2)ε_{ρσ}S^{ρσ})γ^{μ}(1 + (1/2)ε_{ρσ}S^{ρσ}) = (1 + (1/2)ε_{ρσ}M^{ρσ})γ^{ν}
(1  (1/2)ε_{ρσ}S^{ρσ})(γ^{μ} + (1/2)ε_{ρσ}S^{ρσ}γ^{μ}) = (1 + (1/2)ε_{ρσ}M^{ρσ})γ^{ν}
γ^{μ} + (1/2)ε_{ρσ}S^{ρσ}γ^{μ}  (1/2)ε_{ρσ}S^{ρσ}γ^{μ} + O(ε_{ρσ}^{2}) = γ^{μ} + (1/2)ε_{ρσ}M^{ρσ}γ^{ν}
(S^{ρσ}γ^{μ}  S^{ρσ}γ^{μ}) = M^{ρσ}γ^{ν}
[S^{ρσ},γ^{μ}] = (M^{ρσ})^{μ}_{ν}γ^{ν}
Using 11. on the LHS and 5. on the RHS gives:
γ^{μ}η^{νρ}  γ^{ν}η^{ρμ} = (η^{ρμ}δ^{σ}_{ν}  η^{σμ}δ^{ρ}_{ν})γ^{ν}
γ^{μ}η^{νρ}  γ^{ν}η^{ρμ} = η^{ρμ}γ^{σ}  η^{σμ}γ^{ρ}
_
So we have proven 13. and ψγ^{μ}ψ does indeed transform
as a vector.
Tensor

To form a tensor (spin 2) from two spinors one writes:
_
ψS^{μν}ψ
Under a Lorentz transformation,
_
ψS^{μν}ψ > ψS[Λ]^{1}S^{μν}S[Λ]ψ
_
= ψS[Λ]^{1}((1/2)[γ^{μ},γ^{ν}])S[Λ]ψ
_
= (1/2)ψS[Λ]^{1}(γ^{μ}γ^{ν}  γ^{ν}γ^{μ})S[Λ]ψ
_
= ψ(1/2)(S[Λ]^{1}γ^{μ}S[Λ]S[Λ]^{1}γ^{ν}S[Λ]
 S[Λ]^{1}γ^{ν}S[Λ]S[Λ]^{1}γ^{μ}S[Λ])ψ
Now from 13. S[Λ]^{1}γ^{μ}S[Λ] = Λ^{μ}_{ν}γ^{ν}
ψS^{μν}ψ > ψ(1/2)(Λ^{μ}_{α}γ^{α}Λ^{ν}_{β}γ^{β}  Λ^{ν}_{β}γ^{β}Λ^{μ}_{α}γ^{α})ψ
_
= ψ(1/2)Λ^{μ}_{α}Λ^{ν}_{β}[γ^{α},γ^{β}]ψ
_
= Λ^{μ}_{α}Λ^{ν}_{β}ψS^{αβ}ψ
_
So ψS^{μν}ψ does indeed transform as a tensor.
Generalization

Consider the expression:
_
ψΓ^{A}ψ
We have already found expressions for scalars,
vectors and tensors. Can we find Γ^{A}'s that
create other objects that transform correctly
under a Lorentz transformation. Again, the
answer is yes. We can write Γ^{A} in terms of the
following combinations of 16 γ matrices.
Γ^{A} =
1 ^{ } : scalar (1 component)
γ^{μ} ^{ } : vector (4 components)
S^{μν} = (i/2)[γ^{μ},γ^{ν}] : Tensor (6 components)
γ^{μ}γ^{5} ^{ } : pseudovector (4 components)
γ^{5} ^{ } : pseudoscalar (4 component)
Spinor Indeces

Consider the Weyl spinors mentioned above and
define:
 
ψ_{L} =  ξ_{α} 
_{ }  0_{ } 
 
 
ψ_{R} =  0^{ }
_{ }  _^{ }
_{ }  χ^{α'}
 
 
ψ = ψ_{L} + ψ_{R} =  ξ_{α}_{ }
_{ }  __{ }
_{ }  χ^{α'}
 
This is the VAN DER WAERDEN NOTATION.
α = lefthanded spinor index.
α' = right handed spinor index.
_ does not mean conjugate  it is purely notation.
We can further define:
_
ξ_{α'} = (ξ_{α})^{†}
and,
_
χ^{α} = (χ^{α'})^{†}
_ 
ψ^{†} =  ξ_{α'} 
^{ }  χ^{α}^{ } 
 
_
Now, ψ = γ^{0}ψ^{†}
   
Where γ^{0} =  0 I_{2}  =  0 1  in the Weyl representation.
^{ }  I_{2} 0   1 0 
   
_    _ 
ψ =  0 1  ξ_{α'} 
 1 0  χ^{α}^{ } 
   
 _ 
=  χ^{α} ξ_{α'} 
 
Spinor indices are raised and lowered using the
antisymmetric symbol, ε, that has the properties:
ε^{12} = ε^{21} = ε_{21} = ε_{12} = 1
ε^{11} = ε^{22} = ε_{11} = ε_{22} = 0
ε^{ab}ε_{bc} = δ^{a}_{c} = 1
ε_{ab}ε^{bc} = δ_{a}^{c} = 1
ε^{a'b'}ε_{b'c'} = δ^{a'}_{c'} = 1
ε_{a'b'}ε^{b'c'} = δ_{a'}^{c'} = 1
In matrix form:
 
ε_{αβ} = ε_{α'β'} =  0 1  = iσ_{2}
_{ }  1 0 
 
 
ε^{αβ} = ε^{α'β'} =  0 1  = iσ_{2}
_{ }  1 0 
 
We can use these operators as follows:
_ _ _ _
ξ_{α} = ε_{αβ}ξ^{β} ξ^{α} = ε^{αβ}ξ_{β} χ_{α'} = ε_{α'β'}χ^{β'} χ^{α'} = ε^{α'β'}χ_{β'}
Therefore,
ε_{αβ}ξ^{β} = ξ_{α}
     
 0 1  ξ^{α}  =  0_{ } 
 1 0  0_{ }   ξ_{α} 
     
ε^{αβ}ξ_{β} = ξ^{α}
     
 0 1  ξ_{α}  =  0_{ } 
 1 0  0_{ }   ξ^{α} 
     
Note: ε^{αβ} = ε^{α'β'} etc. ε^{α'β} and ε^{αβ'} are not allowed.
Therefore, the Dirac Lagrangion excluding the mass term
is:
 _      _ _ _
L = i χ^{α} ξ_{α'}  0 σ_{μ}  ∂_{μ}ξ_{α}^{ }  = iχ^{α}σ^{μ}∂_{μ}χ^{α'} + ξ_{α'}σ_{μ}∂_{μ}ξ_{α}
 ^{ }   _^{ }  _^{ }
^{ }  σ_{μ} 0  ∂_{μ}χ^{α'} 
   
^

γ^{μ} in the Weyl representation.
Spinor Transformations

Let us now reconstruct the spinor transformation laws
that incorporate indeces.
   
In the Weyl basis γ^{μ} =  0 σ^{k}  >  0 σ^{μ} 
^{ }  σ^{k} 0   _^{ } 
^{ }    σ^{μ} 0 
 
Where,
σ^{μ} = (1,σ^{i}) is substituted for σ_{k}
_
σ^{μ} = (1,σ^{i}) is substituted for σ_{k}
Which for rotations leads to:
   
S^{μν} = (1/4) 0 σ^{μ}  0 σ^{ν} 
^{ }  _ ^{ }  _ ^{ } 
^{ }  σ^{μ} 0  σ^{ν} 0 
   
 _ _ 
= (1/4) σ^{μ}σ^{ν}  σ^{ν}σ^{μ} 0 
 _{ } _ _ 
 0 σ^{μ}σ^{ν}  σ^{ν}σ^{μ} 
 
The objects that obey the Lorentz algebra and generate
the desired rotations are given by:
_ _
(S^{μν})_{α}^{β} = (1/4)(σ^{μ}σ^{ν}  σ^{ν}σ^{μ})_{α}^{β}
_ _ _
(S^{μν})^{α'}_{β'} = (1/4)(σ^{μ}σ^{ν}  σ^{ν}σ^{μ})^{α'}_{β'}
So these correspond to:
ξ_{α} > (exp((1/2)Ω_{μν}S^{μν}))_{α}^{β}ξ_{β}
and,
_ _
χ^{α'} > (exp((1/2)Ω_{μν}S^{μν}))^{α'}_{β'}χ^{β'}
Which is the same as the rotational transformation
that we derived in Spinors  Part 1.
Parity

Parity is the operation of changing coordinates as:
x^{0} > x^{0} x^{i} > x^{i}
Under parity, the left and righthanded spinors are
exchanged. Under parity, rotations don’t change sign
but boosts flip sign. Therefore,
Pψ_{L,R}(t,x) = ψ_{R,L}(t,x)
_{ } = γ^{0}ψ_{R,L}(t,x)
if ψ(t,x) satisfies the Dirac equation, then the
parity transformed spinor γ^{0}ψ(t,x) also satisfies
the Dirac equation, meaning:
(iγ^{0}∂_{t} + iγ^{i}∂_{i}  m)γ^{0}ψ(t,x) = γ^{0}(iγ^{0}∂_{t}  iγ^{i}∂_{i}  m)γ^{0}ψ(t,x)
Where the extra minus sign from passing γ^{0} through
γ^{i} is compensated by the derivative
acting on x instead of +x.
Thus, in the Weyl basis we have:
     _ 
ψ^{P} =  0 1  ξ_{α}^{ }  =  χ^{α'} 
^{ }  1 0  _^{ }   ξ_{α}^{ } 
^{ }    χ^{α'}   
 
Charge Conjugation

Charge conjugation is the operation of changing every
particle into its antiparticle. It is a discrete
symmetry and represents the 'C' in the CPT (Charge,
Parity, Time Reversal) symmetry. Charge conjugation is
accomplished using the charge conjugation operator, C:
_
ψ^{C} = Cψ^{T}
Where C is defined as the matrix:
   
C =  iσ_{2} 0  =  ε_{αβ} 0^{ }
 0 iσ_{2}   0 ε^{α'β'}
   
C satisfies C^{T} = C^{†} = C^{1} = C and has the property
C^{1}ψC = ψ^{C}
So for our spinor, ψ, we get:
_  
ψ^{T} =  χ^{α}^{ } 
^{ }  _^{ } 
^{ }  ξ_{α'} 
 
     
 ε_{αβ} 0^{ } χ^{α}^{ }  =  ε_{αβ}χ^{α}_{ }
 0 ε^{α'β'} _^{ }  _{ } _ 
_{ }   ξ_{α'}   ε^{α'β'}ξ_{α'}
   
 
=  χ_{β}^{ }
 _^{ }
 ξ^{β'}
 
   
 ξ_{α}_{ }   χ_{β}^{ }
 __{ }  < h.c. >  _^{ }
 χ^{α'}   ξ^{β'}
   
Therefore, the Hermitian conjugate of any left handed
Weyl spinor is a right handed Weyl spinor and vice
versa.
Scalars, Vectors and Tensors

Scalars

We can form a scalar out of 2 Weyl spinors as follows:
_ _
ξχ ≡ ξ^{α'}χ_{α'}
_
= ξ^{α'}ε_{α'β'}χ^{β'}
_
= χ^{β'}ε_{α'β'}ξ^{α'} ( because χ and ξ anticommute)
_
= χ^{β'}ε_{β'α'}ξ^{α'}
_
= χ^{β'}ξ_{β'}
_
= χξ
Similarly,
ξχ ≡ ξ^{α}χ_{α}
= ξ^{α}ε_{αβ}χ^{β}
= χ^{β}ε_{αβ}ξ^{α} ( because χ and ξ anticommute)
= χ^{β}ε_{βα}ξ^{α}
= χ^{β}ξ_{β}
= χξ
Note the positive sign in accordance with the spin
statistics theorem.
Vectors

Rewrite:
σ^{μ} = (σ^{μ})_{αα'}
_ _
σ^{μ} = (σ^{μ})^{αα'}
Such that,
_
σ^{μαα'} = ε^{αβ}ε^{α'β'}σ^{μ}_{ββ'}
We can now form a vector out of 2 Weyl spinors as
follows:
ξσ^{μ}χ ≡ ξ^{α}σ^{μ}_{αα'}χ^{α'}
_
= χ^{α'}σ^{μ}_{αα'}ξ^{α}
_
= ε^{α'β'}χ_{β'}σ^{μ}_{αα'}ε^{αβ}ξ_{β}
_
= ε^{α'β'}χ_{β'}σ^{μ}_{αα'}ε^{αβ}ξ_{β}
_
= χ_{β'}(ε^{β'α'}ε^{βα})σ^{μ}_{αα'}ξ_{β}
_ _
= χ_{β'}σ^{μβ'β}ξ_{β} (σ^{μ}_{αα'} = (1,σ^{i}) and σ^{μαα'} = (1,σ^{i}))
__
= χσ^{μ}ξ
Note the negative sign in accordance with the spin
statistics theorem.